Dance composition basics - Pamela Sofras (Champaign, IL : Human Kinetics, 2020)
"Designed for beginning college-level dance composition courses and dance courses at the middle and high school levels, this textbook and its ancillaries highlight selected portions of original dance compositions by two famous choreographers"-- Provided by publisher
Keywords: Choreography; Textbooks